Bilateral iPhone Gorilla Glass Intraocular Foreign Bodies in a Pediatric Patient. (January 2021) - Kalavar, Meghana; Levitt, Alexandra; Patel, Nimesh A.; Clauss, Kevin; Fan, Kenneth C.; Yannuzzi, Nicolas A.; Berrocal, Audina M.
Purpose: This report discusses a case of a patient with bilateral intraocular foreign bodies after a bullet shattered his iPhone. Methods: A case report is presented. Results: The right eye vision was 20/50 and examination disclosed a limbal entry wound at 6:00, dense traumatic cataract, and vitreous hemorrhage. The left eye was 20/40 and an entry wound located roughly 4 mm posterior to the limbus was noted. Fundoscopy revealed multiple refractile particles with preretinal and vitreous hemorrhage. Computed tomography scan demonstrated hyperdensities in the vitreous cavity bilaterally. Globe closure, cataract removal, vitrectomy, and endolaser were undertaken in the right eye, while only globe closure was performed in the left eye. On latest follow-up, the patient had 20/20 corrected vision without inflammation bilaterally. Conclusion: A conservative approach led to full visual recovery, despite retained intraocular smartphone Gorilla glass.